Continuous glucose monitoring in older people with diabetes and memory problems: a mixed-methods feasibility study in the UK. Issue 11 (18th November 2019) - Mattishent, Katharina; Lane, Kathleen; Salter, Charlotte; Dhatariya, Ketan; May, Helen M; Neupane, Sankalpa; Loke, Yoon K
Abstract : Objectives: Older people with diabetes are at increased risk of harm from hypoglycaemia, particularly where there are coexisting memory problems. Continuous glucose monitoring (CGM) offers important benefits in terms of detecting hypoglycaemia, but the feasibility of use and extent of data capture has not been tested in this patient group. Our objective was to investigate the feasibility of trialling a CGM intervention in the community setting in older people with diabetes and memory problems. Design: Mixed-methods feasibility study. Setting: Community dwellings in the UK. Participants: Patients aged ≥65 with diabetes and abbreviated mental test score ≤8 or known dementia. Intervention: FreeStyle Libre CGM. Primary and secondary outcome measures: Feasibility criteria were numbers of eligible patients, recruitment, attrition, extent of capture of glucose readings and adverse events. Qualitative interview. Results: We identified 49 eligible participants; 17 consented, but 5 withdrew before recording of data because they or their carers felt unable to manage study procedures. 12 participants (mean age 85 years) completed the study without adverse events. Data capture across 14 days ranged between 3% and 92% (mean 55%); 6 participants had <60% capture. Hypoglycaemic events were recorded in six out of nine insulin users. Qualitative interviews found: the device does not interfere with daily activities, usability and comfort was positive, and it was helpful for carers in monitoring participants' glucose concentrations. Conclusions: The device was acceptable to participants, and carers reported greater ease in monitoring the participant's glucose concentrations. However, completeness of data capture varied considerably with this device due to the need for users to conduct ≥3 scans per day. Real-time devices with automated data transfer may be more suitable in older people with memory problems.